TO THE QUESTION OF THE RECREATIONAL SPACE FORMATION (ON THE EXAMPLE OF THE REPUBLIC OF CRIMEA) - E. G. Matyugina; O. V. Pogharnitskaya; O. V. Vusovich (Юг России: экология, развитие)
Aim. The aim of the research is to identify the specifics of the attractiveness of the recreational space of resort areas for the sub-federal units of different levels.Methods. In the research of approaches to the organization of recreation and structural features of the territorial space, we applied systematic and analytical comparativegeographical methods of analysis on the example of the Republic of Crimea.Findings. The urgency of integration of the compensatory mechanism into the reproduction processes determines the importance of not only the allocation of recreational space, but also the organization of purposeful activities to ensure and maintain its attractiveness. Since the resort areas have been adopted as a research object, it is necessary to rank the components of the natural resource potential on the basis of their participation in building recreation. A wide range of forms of manifestation of recreational interest determines the positioning of the basic and complementary types of recreation. The attractiveness of the latter takes various forms depending on the subject-carrier of interest.Conclusion. In the formation of a recreational space, it is necessary to define the "profiling" of the territory in terms of identifying the most significant component that is the basis for organizing recreational activities, identifying the related areas, thus it provides a greater coverage of the preferences of the sub-federal units. As a result, it gives the recreation a systematic property based on the integrated and maximally full use of the potential of the territory. Recreational space is studied in terms of the formation of the structure of the actual recreation ("recreation pyramid") and infrastructure, hence only their compilation provides the attractiveness of the recreation. Has been proved the existence of various forms of attractiveness of recreational space for economic entities of different levels. These conditions, examined on the example of the Republic of Crimea, can be used to assess the attractiveness of other recreational spaces as well, both the analogous profile and other areas of recreation.